Normative values and changes in range of motion, strength, and functional performance over 1 year in adolescent female football players: Data from 418 players in the Karolinska football Injury Cohort study. (November 2022) - Fältström, Anne; Skillgate, Eva; Tranaeus, Ulrika; Weiss, Nathan; Källberg, Henrik; Lyberg, Victor; Nomme, Mathias; Thome, Nicolai; Omsland, Truls; Pedersen, Eirik; Hägglund, Martin; Waldén, Markus; et al.
Abstract: Objective: To study normative values of range of motion (ROM), strength, and functional performance and investigate changes over 1 year in adolescent female football players. Design: Cross-sectional. Participants: 418 adolescent female football players aged 12–17 years. Main outcome measures: The physical characteristic assessments included (1) ROM assessment of the trunk, hips, and ankles; (2) strength measures (maximal isometric and eccentric strength for the trunk, hips, and knees, and strength endurance for the neck, back, trunk and calves), and (3) functional performance (the one-leg long box jump test and the square hop test). Results: Older players were stronger, but not when normalized to body weight. Only small differences in ROM regarding age were found. ROM increased over 1 year in most measurements with the largest change in hip external rotation, which increased by 6–7° (Cohen's d = 0.83–0.87). Hip ( d = 0.28–1.07) and knee ( d = 0.38–0.53) muscle strength and the square hop test ( d = 0.71–0.99) improved over 1 year. Conclusions: Normative values for ROM and strength assessments of neck, back, trunk, hips, knees, calves and ankles are presented for adolescent female football players. Generally, fluctuations in ROM were small with little clinical meaning, whereas strength improved over 1 year. Highlights: Normative values for clinical and functional tests in adolescent female football players. Range of motion did not change over 1 year. Older players were stronger, but not when normalized to body weight. Female adolescent players improved in hip abduction strength and square hop test over 1 year.